Implementation of the Full-Day School Education System at Al-Qudwah Integrated Islamic Elementary School - Wahid, Jamrul; Ruslan, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
Al-Qudwah Integrated Islamic Elementary School is an Islamic educational institution that has been established since 2018 and accepted its first batch in that year. This school also implements a full-day education system, which provides more time for students to study various subjects, both religious and general. The purpose of this study is to determine the implementation of the full-day school education system at Al-Qudwah Integrated Islamic Elementary School, Shah Alam, the obstacles to implementing the full-day school education system at Al-Qudwah Integrated Islamic Elementary School, Shah Alam, and the opportunities and challenges of the full-day school education system at Al-Qudwah Integrated Islamic Elementary School, Shah Alam. The research method used is a descriptive qualitative research type. Qualitative research is an inquiry approach that emphasizes the search for meaning, understanding, concepts, characteristics, symptoms, symbols or descriptions of a natural phenomenon. The results of this study are developing students' academic skills and personalities based on Islamic teachings. So it is hoped that the full-day education system can realize students' moral personalities to be even better.